UBR-5, a Conserved HECT-Type E3 Ubiquitin Ligase, Negatively Regulates Notch-Type Signaling in Caenorhabditis elegans. Issue 7 (1st July 2016) - Safdar, Komal; Gu, Anniya; Xu, Xia; Au, Vinci; Taylor, Jon; Flibotte, Stephane; Moerman, Donald G; Maine, Eleanor M
Abstract: Notch-type signaling mediates cell−cell interactions important for animal development. In humans, reduced or inappropriate Notch signaling activity is associated with various developmental defects and disease states, including cancers. Caenorhabditis elegans expresses two Notch-type receptors, GLP-1 and LIN-12. GLP-1 mediates several cell-signaling events in the embryo and promotes germline proliferation in the developing and adult gonad. LIN-12 acts redundantly with GLP-1 in certain inductive events in the embryo and mediates several cell−cell interactions during larval development. Recovery of genetic suppressors and enhancers of glp-1 or lin-12 loss- or gain-of-function mutations has identified numerous regulators of GLP-1 and LIN-12 signaling activity. Here, we report the molecular identification of sog-1, a gene identified in screens for recessive suppressors of conditional glp-1 loss-of-function mutations. The sog-1 gene encodes UBR-5, the sole C. elegans member of the UBR5/Hyd family of HECT-type E3 ubiquitin ligases. Molecular and genetic analyses indicate that the loss of ubr-5 function suppresses defects caused by reduced signaling via GLP-1 or LIN-12. In contrast, ubr-5 mutations do not suppress embryonic or larval lethality associated with mutations in a downstream transcription factor, LAG-1. In the gonad, ubr-5 acts in the receiving cells (germ cells) to limit GLP-1 signaling activity. SEL-10 is the F-box component of SCF SEL-10 E3 ubiquitin–ligase complex that promotes turnover of Notch intracellular domain. UBR-5 acts redundantly with SEL-10 to limit Notch signaling in certain tissues. We hypothesize that UBR-5 activity limits Notch-type signaling by promoting turnover of receptor or limiting its interaction with pathway components.